Interactive e-student worksheet based on computational thinking with South Sumatera Traditional Game context - Ostian, Dyego; Hapizah, Hapizah; Mulyono, Budi (Jurnal Pendidikan Matematika RAFA, 2023)
This research aims to develop an interactive e-student worksheet on integers in the context of traditional South Sumatran games that is valid and practical. This research was carried out at SMP in Martapura class VII in the odd semester of the 2023/2024 academic year. This research uses a type of development research (Research and Development) using the ADDIE model but researchers only use three stages, namely Analysis, Design and Development. The validity of the interactive e-student worksheet is checked through 3 factors, namely construct, content and language contained in the validation sheet at the Expert Review stage and input or comments from the experimental results at the One to One stage. The practicality of interactive e-student worksheet is based on the results of questionnaire calculations given at the Small Group stage. The results of the research show that the development of interactive e-student worksheet has a validity of 95.3125% with very valid criteria and a practicality percentage of 86.25% which is classified as very practical